Effects of non-electrical parameters on profile accuracies and surface characteristics during wire-EDM of titanium alloy. Issue 6 (28th October 2021) - Kirwin, Roan M.; Jahan, Muhammad P.
Abstract: Wire lag plays a major role in causing inaccuracies in certain geometrical shapes and profiles during machining of complex structures using wire-EDM. While previous studies focused on investigating effects of electrical parameters on machining performance and accuracy during wire EDM, the effects of non-electrical parameters on corner and profile accuracies have not been studied comprehensively. The objective of this study is to investigate effects of non-electrical parameters on the geometric and profile accuracies as well as surface and subsurface characteristics during WEDM of Ti-6Al-4V alloy. A complex part including corners with 45°, 90°, and 112.5° as well as thin wall section for measuring the kerf accuracy was designed. It is found that the profile accuracy improves as the wire tension increases. However, too high wire tension results in curved path in the sharp corners. The effect of wire tension is more pronounced on the workpiece with higher thickness. Too high wire feed rate reduces the accuracy for target angles, especially for lower thickness of workpiece. The kerf width is smaller for thinner workpiece and improves with lower wire feed rate and wire tension. While the wire tension and wire feed rate do not have an impact on surface roughness, higher surface feed rate increases surface roughness. Higher wire tensions lead to higher surface cracking due to more rapid cooling. With increase of surface feed, the percentage of arcing pulses increases due to increased instability, which results in rougher surface and increased percentage of beta phases at the subsurface.